Outcomes of Dyslipidemia Screening Program in School-aged Children - Engin Köse; Melis Köse; Sipil Topçu; Büşra Matur; Buket Barış; Behzat Özkan (Journal of Pediatric Research)

(untitled)
Aim:Screening of dyslipidemia in childhood has been controversial. While some guidelines recommend screening for dyslipidemia in children, others emphasize that there is insufficient evidence for screening for dyslipidemia in those less than 20 years of age. In this study, we aimed to evaluate the outcomes of a lipid screening program and reveal the pros and cons of this program.Materials and Methods:All patients referred to a paediatric metabolism outpatient clinic by family physicians with the suspicion of dyslipidemia in a lipid screening program at schools were investigated. Demographic and physical examination findings, screening lipid profiles and fasting control lipid profiles of the patients were evaluated. The definitive diagnosis with fasting lipid profile and genetic analysis were recorded.Results:Two hundred seventy-four patients suspected with dyslipidemia were enrolled in the study. The mean age of study group was 9.2±3.2 (5-17) years. While 158 (57.7%) patients were admitted with high total cholesterol (TC) and low-density lipoprotein cholesterol, high triglyceride level was detected in 58 (21.2%) patients via a paediatric lipid screening program. A high TC level was revealed in 26 (9.5%) patients. With the control fasting lipid profile, 100 (36.5%) patients had a normal lipid profile. Fifty-nine (21.5%) patients were diagnosed with familial hypercholesterolemia (FH), and hyperchylomicronemia and hypobetalipoproteinemia were revealed in 5 (1.8%) and 4 (1.5%) patients, respectively. Eleven patients diagnosed with FH did not declare hyperlipidemia in parents. In a screening of these patients’ immediate families, 11 parents and 3 siblings were diagnosed with familial hyperlipidemia.Conclusion:This is the first study performed to date that evaluated the outcomes of a lipid screening program on school age children in Turkey. We found that this screening program is effective in diagnosing not only the patients but also asymptomatic parents and siblings. Evaluation and verification of dyslipidemia should be performed under fasting conditions to avoid false positive results.